2016
DOI: 10.1080/03069885.2016.1164297
|View full text |Cite
|
Sign up to set email alerts
|

Responding to self-harm in the school setting: the experience of guidance counsellors and teachers in Ireland

Abstract: School-based studies identify that while one in ten young people engages in self-harm, only a small minority seek professional help. School counsellors and teachers are potentially the only professionals who may be aware of a young person's self-harm, however little is known about how this impacts on them and how they might be best supported to respond to distressed students. This study employed a qualitative descriptive design to explore postprimary school teachers' and guidance counsellors' (n=6) experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…Meanwhile a lack of training was cited as one of the most significant barriers to effectively addressing the issue. Similar findings have been reported elsewhere (Berger et al., 2014a, 2014b; Dowling & Doyle, ), with a survey of teachers in Australia finding that 41% require improved staff education and school policy frameworks (Berger et al., 2014a).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Meanwhile a lack of training was cited as one of the most significant barriers to effectively addressing the issue. Similar findings have been reported elsewhere (Berger et al., 2014a, 2014b; Dowling & Doyle, ), with a survey of teachers in Australia finding that 41% require improved staff education and school policy frameworks (Berger et al., 2014a).…”
Section: Discussionsupporting
confidence: 86%
“…A recent systematic review and meta‐ethnography of international qualitative evidence on the role of schools in adolescent self‐harm and suicide found that it is often not prioritised (Evans & Hurrell, ). There is a culture of fear amongst staff (Best, ; Dowling & Doyle, ), with many school professionals feeling ill equipped to manage behaviours (Berger, Hasking, & Reupert, 2014a, 2014b; De Riggi et al., ). This often leads to the escalation of incidents through the hierarchical school structure in the effort to locate ‘expertise’, which often comes from an external source (Berger et al., 2014b; Best, ; McAndrew & Warne, ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings support previous qualitative research that schools rate incidents of self-harm and suicidal behaviour as severe and have a tendency to escalate incidents in an attempt to provide adequate support to the student (Evans & Hurrell, 2016). It has been reported that schools often respond to self-harm incidents in a manner of fear, denial or panic and immediate referral to external supports (Dowling & Doyle, 2016). While involving emergency services may sometimes be necessary for medical attention-particularly when a student is presenting with concurrent self-harm and suicidal behaviours-escalating self-harm incidents to external emergency services when risk is not imminent is advised against in best-practice guidelines (Hasking et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…In the US, substantial work has been done to differentiate the work of guidance counsellors and school counsellors. In various countries the term guidance counsellor (Dowling and Doyle, ), is still utilised, which may be different from the work of a school counsellor in the United States (ASCA, ). Carley and Robin () indicated that school counselling has a focus on providing mental and emotional health services for all youth in the school setting.…”
Section: School Counsellor Rolementioning
confidence: 99%